Detection of Power Quality Disturbances in Distribution Power Systems Using Discrete Wavelet Transformer - شعبان, فيصل; حسامو, عصام; عبدالله, جعفر (Latakia University Journal -Engineering Sciences Series, 2020)
Monitoring of power quality using digital computers has become of major importance, because it enables to diagnose the different disturbances at both the producer and consumer, and helps the engineer for making the right decision and choosing the more suitable solution to the case under study. Thereby improving power quality problems within the permitted standards. One of the most powerful digital signal processing techniques to evaluate and analyze power quality is wavelet transform. In this paper, discrete wavelet transform was used to detect the power quality disturbances in the distribution network of Metal smelting factory in Lattakia. The mentioned network was modeled in MATLAB-Simulink, then, discrete wavelet transform was applied on the signals extracted from the main bus-bar feeding the factory loads. The results showed the ability of wavelet transform to detect different disturbances. The transients and waveform deformation of voltage signal were monitored accurately.